AHNS Series: Do you know your guidelines? Perioperative antithrombotic management in head and neck surgery. Issue 1 (16th October 2017) - Meyer, Annika; Gross, Neil; Teng, Marita
Abstract: Head and neck surgeons are commonly faced with surgical patients who have underlying medical problems requiring antithrombotic therapy. It is difficult to achieve a balance between minimizing the risk of thromboembolism and hemorrhage in the perioperative period. Data from randomized, controlled trials are limited, and procedure‐specific bleed rates are also difficult to pinpoint. The decision is made more difficult when patients with moderate‐to‐high risk for thromboembolic events undergo procedures that are high risk for bleeding. This is true for many head and neck oncologic surgeries. Furthermore, although elective procedures may be delayed for optimization of antithrombotic medication, emergent procedures cannot. Head and neck surgery often represents the most challenging of all these circumstances, given the potential risk of airway compromise from bleeding after head and neck surgery.